HEGEMONY OF CHEMISTRY LEARNING IN SENIOR HIGH SCHOOL IN BALI PROVINCE - Lanang Wiaratma, I Gusti (E-Journal of Cultural Studies, 2013)
This study was intended to explain the power and the struggle of meaning behind the hegemony taking place in the management of Chemistry learning in the senior high schools developed to be the ones with International status “rintisan sekolah bertaraf internasional” (SMA RSBI) in Bali. This could be observed from the management of Chemistry learning in SMA RSBI in Bali Province which tended to develop the students’ competence in the cognitive domain. This was done to make the students able to pass the national examination and to be the winners in academic competitions. The main theory used in the present study was the theory of hegemony, eclectically supported by several other theories. The method used in the present study was the qualitative method in which the sample was purposively determined. The data were collected through observation, interview, and documentation. The instrument used was an interview guide. The data were analyzed descriptively and qualitatively. The results of the study showed that the management of Chemistry learning was not optimal yet; it tended to be partially developed. The reason was that there was hegemony of the dominating class over the dominated class, hegemony of the teachers over the students. The students did not acquire maximum learning experience as prescribed in the curriculum. What was developed was the students’ competence in the cognitive domain. This took place due to the politics of image which maintained the status quo which tended to comodify education.
Keywords: hegemony, power, learning management, SMA RSBI.